Karakteristik Kepemimpinan Berjiwa Sosiologi Dalam Membangun Pendidikan Pada Abad ke-21 - Keisa Koputri; Sipah Fauziah; Sri Yulia Kartika (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Education in the 21st century shows how the changes that occur in the education system have become digital. It also shows how the presence of globalization has a major influence on education. In this case, leadership is needed in educational organizations that are able to keep up with the times so that they can meet the needs of education in the 21st century. One of them can use sociological leadership as a reference in shaping good leadership characteristics to lead educational organizations in the 21st century. Therefore, the preparation of this journal aims to examine the characteristics of a sociological leader in building education in the 21st century. In this study we used a qualitative approach with the documentation method, namely collecting secondary data obtained from books, articles and journals. The results showed the characteristics of a sociology-minded leader in educational organizations with the characteristics of his social abilities. Helping in building 21st century education through its role shown by paying attention to social welfare, developing skills and integrating technology in learning. The form of implementation can be seen in the leadership of the principal at SMPN 1 Purwakarta, West Java.